THU0633 Temperature sensitivity in patients with rheumatoid arthritis. (15th June 2017) - Mandl, P; Alasti, F; Kerschbaumer, A; Kaltenberger, R; Krennert, T; Supp, GM; Landesmann, U; Smolen, JS; Aletaha, D
Abstract : Background: Studies evaluating weather sensitivity among patients with rheumatoid arthritis (RA) have yielded conflicting results. Objectives: To evaluate whether patients with RA exhibit sensitivity to outside temperature. Methods: We assessed correlation between mean daily temperature and self-reported pain (by visual analogue scale), and patient's global assessment of disease activity (PGA). Assessments documented in the RA database of our department as well as the average temperature obtained from the Central Institute for Meteorology and Geodynamics, were matched on a daily basis for a period of 10 years between 2005 and 2015 and analyzed using generalized estimating equation (GEE) and a mixed model analysis (MM). Patients with <5 visits in the study period, or with <1 visit/quarter or with pain=0 in ≥3 consecutive visits and those living outside of the catchment area were excluded. Overlap between responsiveness of pain or PGA to temperature was calculated by Cohen's kappa. Results: A total of 399 patients with RA (average disease duration at first visit: 6.0±7.6 years, average age: 57.7±13.9 years, 82% female, mean CDAI 19.7±11.5, 59.9% rheumatoid factor positive) were analyzed. Lower temperatures correlated significantly with higher pain levels (estimate: -0.07, p=0.021) in GEE, however the effect size was very small. When we performed MM with temperature as independent variable and VAS pain or PGA as dependent variable, the majority of patients showed no sensitivity to temperature, however 22% of patients were significantly sensitive to cold temperature with an estimate of -0.29 (p<0.0001) for pain and -0.21 (p=0.0005) for PGA (Figure 1 ). When we evaluated whether patients who demonstrate temperature-sensitivity to pain also exhibit temperature-sensitivity to PGA, we found an excellent overlap between the two patient groups (kappa: 0.81). Conclusions: Our results indicate that a subgroup of patients with RA show significant sensitivity to cold temperature, and that these patients are characterized by higher pain and PGA levels at lower daily temperatures. These aspects may have to be taken into account in longitudinal analyses of disease activity of RA. Disclosure of Interest: None declared